Fakta-Fakta Sosial dalam Lagu-Lagu Madura sebagai Pendukung Pemahaman Wawasan Budaya bagi Siswa SMA - Fiyan Ilman Faqih; Albitar Septian Syarifudin; Arief Setyawan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Study of the social facts contained in Madurese songs can contribute to developing an understanding of cultural insight, especially Madurese culture. This research aims to examine the social facts contained in Madurese songs and how these facts can support the understanding of cultural insight for high school students in Madura. The approach in this research is a qualitative approach. This research using qualitative methods aims to thoroughly understand the characteristics of the side effects felt by the research subjects. The research results in this study are divided into two, namely material and non-material social facts. However, the data produced in material social facts does not exist. Meanwhile, non-material social facts received 13 data consisting of morality, collective consciousness, collective representation and social flows. The social facts that appear in the 7 Madura songs are non-material social facts. These Madurese songs contain non-material social facts consisting of morality, collective consciousness, collective representation and social flows. The results of the analysis of non-material social facts contained in these songs can be used by teachers to be used as teaching material in learning in Phase F so that they can support the understanding of cultural insight for high school students.